2017
DOI: 10.1038/s41565-017-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial resistance to silver nanoparticles and how to overcome it

Abstract: Silver nanoparticles have already been successfully applied in various biomedical and antimicrobial technologies and products used in everyday life. Although bacterial resistance to antibiotics has been extensively discussed in the literature, the possible development of resistance to silver nanoparticles has not been fully explored. We report that the Gram-negative bacteria Escherichia coli 013, Pseudomonas aeruginosa CCM 3955 and E. coli CCM 3954 can develop resistance to silver nanoparticles after repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
523
2
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 744 publications
(550 citation statements)
references
References 33 publications
21
523
2
4
Order By: Relevance
“…[9,10] Considering this concern, great efforts have been made in recent years to develop antimicrobial implant surfaces that rely on the modification of physicochemical properties to interfere with the microbial colonization process. [14] Therefore, it is urgent to develop innovative and creative solutions to eliminate alreadyformed biofilms safely without producing bacterial resistance within a short period of time. ), or resisting bacterial adhesion through electrostatic repulsion and super-hydrophobicity of surface components.…”
mentioning
confidence: 99%
“…[9,10] Considering this concern, great efforts have been made in recent years to develop antimicrobial implant surfaces that rely on the modification of physicochemical properties to interfere with the microbial colonization process. [14] Therefore, it is urgent to develop innovative and creative solutions to eliminate alreadyformed biofilms safely without producing bacterial resistance within a short period of time. ), or resisting bacterial adhesion through electrostatic repulsion and super-hydrophobicity of surface components.…”
mentioning
confidence: 99%
“…Moreover, although such strategies might be helpful to decrease AgNP migration into food, they would do little or nothing to reduce environmental effects of discarded AgNPs . Another important issue with AgNP that should be considered is resistance developed by G(−) bacteria upon repeated long‐term exposure to AgNP, which results from production of flagellin, a protein that promotes AgNP aggregation . On the other hand, the study demonstrated that pomegranate rind extract, which inhibits flagellin production, could suppress bacterial resistance to AgNPs, allowing the repeated long‐term antimicrobial action of such antimicrobial agent.…”
Section: Inorganic Antimicrobial Nanostructuresmentioning
confidence: 99%
“…This resistance stems from the production of the adhesive flagellum protein flagellin, which triggers the aggregation of NPs and thereby eliminating the antibacterial effect on gram negative bacteria. (Panacek et al, ). These findings clarify a mechanism that can drive bacterial resistance to antibacterial agents.…”
Section: Mechanisms Of Silver Nanoparticle Antibacterial Toxicitymentioning
confidence: 99%